Comparison of the effects of dexmedetomidine administered at two different times on renal ischemia/reperfusion injury in rats - Gonullu,Edip (2014)
Background and objectives: We investigated the effect of dexmedetomidine on ischemic renal failure in rats. Methods: In the present study, 26 male adult Wistar albino rats weighting 230-300 g were randomly separated into four groups: sham-operated (n = 5), ischemia reperfusion (IR) (IR group, n = 7), IR/reperfusion treatment with dexmedetomidine (Dex. R group, n = 7) and IR/pre-ischemic treatment with dexmedetomidine (Dex. I group, n = 7). In the first group, sham operation was achieved and renal clamps were not applied. For the IR group, renal ischemia was induced by occlusion of the bilateral renal arteries and veins for 60 min followed by reperfusion for 24 h. For the Dex. R and Dex. I groups, the same surgical procedure as in the IR group was performed, and dexmedetomidine (100 mcg/kg intraperitoneal) was administrated at the 5th min after reperfusion and before ischemia. At the end of reperfusion, blood samples were drawn, the rats were sacrificed, and the left kidney was processed for histopathology. Results: The blood urea nitrogen (BUN) levels in groups Dex. R and Dex. I were significantly lower than in the IR group (p = 0.015, p = 0.043), although urine flow was significantly higher in group Dex. R (p = 0.003). The renal histopathological score in the IR group was significantly higher than in the other groups. There was no significant difference between the Dex. R and Dex. I groups. Conclusions: The results were shown that administration of dexmedetomidine reduced the renal IR injury histomorphologically. Administration of dexmedetomidine in the reperfusion period was considered as more effective due to increase in urinary output and decrease in BUN levels.